Lexical Cohesion Roles In Speech Rhetorical Strategy of 2016 U.S Presidential Debate, Trump Vs Clinton - Saefudin Saefudin (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2020)
This research aims at describing the speech text cohesion and its contribution to the rhetorical strategy used in the 2016 U.S Presidential debate between Trump and Clinton in their first campaign debate on the political topic area on achieving prosperity, America's direction, and securing America. As an effort to reach the purpose of research, the researcher applies qualitative descriptive method on Discourse Analysis (D.A.) as the theory to describe and analyze the lexical cohesion relation and rhetorical devices linguistically used in the discourse of presidential debate. Furthermore, based on the analysis, the data were found around 399 lexical cohesion devices of reiteration and 64 collocations used by Clinton, and as many as 576 lexical cohesion devices for reiteration and 58 markers of collocation relations were applied by Trump in the debate over U.S presidential debates. Repetition is the most dominant type of lexical cohesion at U.S presidential debate, both realized by Clinton and Trump. The repetition achieved by both debate partners was 39.74% and 63.25%. Some of the lexical relation roles used by the two pairs of candidates based on the topics discussed reveal some differences in their political objectives, namely, economic and industrial issues, law, trade, investment, labor, taxes, and terrorism. Meanwhile, the rhetorical tools used by the two candidate pairs include; metaphor, a list of three, parallelism, and contrastive pairs (antithesis). In addition, the debate rhetoric technique used by both candidates includes; anaphora, epiphora, and climax.